Comparison of The Effects of Broiler and Domestic Chicken Meat on Serum Testosterone and Luteinizing Hormone Levels in Rats - Khan, Hamad Gul; Rashid, Amir; Khan, Saleem Ahmed; Yousaf, Muhammad Javad; Aman, Faiza; Shoaib, Muhammad (Journal of Ayub Medical College Abbottabad, 2019)
Background: The aim of study is to evaluate and compare the effects of broiler chicken fed with commercially available feed and chicken fed with organic diet on serum testosterone and Luteinizing Hormone levels in Sprague Dawley rats. It was a randomized controlled trial conducted in Multi-Disciplinary Laboratory of Department of Biochemistry and Molecular Biology, Army Medical College, Rawalpindi, in collaboration with Quaid-e-Azam University, Islamabad from November 2017 to April 2019. Methods: Ninety male early weaned Sprague Dawley rats were randomly assorted into three groups (n=30). Group I control rats were nourished on standard pelleted diet. Group-II rats were nourished with organic chicken meat along with their standard pelleted diet. Group-III rats were nourished with broiler chicken meat along with their standard pelleted diet. Serum Testosterone and Luteinizing Hormone levels were estimated through ELISA. Weight gain and the % growth rate were also estimated. Mean±SD values of all variables were calculated. One-way ANOVA was applied to determine the significance among groups followed by Tuckey's HSD post hoc test. p value ‰¤0.05 was considered significant. Results: The current study demonstrated significant increase in serum Testosterone levels (p=0.002) and a significant decrease in serum Luteinizing Hormone levels (p=0.003) between control and broiler meat fed rats (Group-III). The study also showed significant increase in weight gain and % growth rate (p<0.001) in both experimental groups as compared to control group. Conclusion: Based on the findings of our study we propose that broiler chicken meat consumption could be the potential cause of hormonal imbalance and out of proportion weight gain and growth in experimental rats. Keywords: Broiler Chicken; Organic Chicken; Serum Testosterone; Luteinizing Hormone; Sprague Dawley Rats; Growth Rate